2004
DOI: 10.1021/ac049476h
|View full text |Cite
|
Sign up to set email alerts
|

Gallium Nitride-Based Potentiometric Anion Sensor

Abstract: The gallium nitride (GaN) semiconductor is used as the sensing element for the development of a potentiometric anion sensor. The anion recognition mechanism is based on the selective interaction of anions in solution with the epitaxial Ga-face polarity GaN (0001) wurtzite crystal film grown on sapphire. The native GaN crystal is used for the development of an ion blocked sensor. The potential is based on the Volta potential, generated at the semiconductor/solution interface and within the Helmholtz layer, due … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
1
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 21 publications
(23 reference statements)
3
21
1
1
Order By: Relevance
“…51.9 AE 3.7 mV/decade and are generally consistent with those reported by Chaniotakis [13,14]. The largest difference occurs for KSCN (À 51.9 AE 3.7 mV/decade in our study versus À 69.5 mV/decade in Chaniotakis [13,14] ).…”
Section: Calibration Plotssupporting
confidence: 91%
See 2 more Smart Citations
“…51.9 AE 3.7 mV/decade and are generally consistent with those reported by Chaniotakis [13,14]. The largest difference occurs for KSCN (À 51.9 AE 3.7 mV/decade in our study versus À 69.5 mV/decade in Chaniotakis [13,14] ).…”
Section: Calibration Plotssupporting
confidence: 91%
“…The linear regions of the GaN electrode in this research are generally of similar magnitude or wider than those reported by Chaniotakis [13,14] with the same electrolyte solutions.…”
Section: Calibration Plotssupporting
confidence: 83%
See 1 more Smart Citation
“…28 Here, anion recognition is based on adsorption processes on the gallium face of the (0001) GaN crystal in analogy to early work on CdS based membranes, but unfortunately the reported ion selectivities were not impressive.…”
Section: Ises: Materials Ionophores Ion-exchangersmentioning
confidence: 99%
“…Redox chemistry is, therefore, not possible for Ga(III) in biological mediums (2). The coordination chemistry of gallium (III) ions has been largely studied in the last decades (3)(4)(5)(6)(7)(8)(9) where many ligands with oxygen and/or nitrogen donor atoms (such as carboxylate, phosphonate, phenolate, hydroxamate and amine groups) were used as chelating agents.…”
Section: Introductionmentioning
confidence: 99%